Uso de membrana biossintética a base de celulose na regeneração tecidual guiada - Iamaguti, Luciana Santini [UNESP]; Brandão, Claudia Valeria Seullner [UNESP] (Universidade Estadual de Londrina (UEL), 2007)
Guided Tissue Regeneration (GTR) is a regenerative treatment modality that requires the placement of a physical barrier over a bone defect in such a way that the proliferation of the surrounding soft tissues into the barrier-protected area is prevented. Thereby in the guided osseous regeneration allowing bone-forming cells from the existent bone edges to invade the space and produce bone. The physical barriers should be biocompatible, allow cellular occlusion, maintain adequate space, tissue integration and facility in the application. They can be occlusive or permeable, absorbable or non-absorbable. Among various types of physical barriers in the market, the cellulose biosynthetic membrane is emphasizing by the necessary characteristics for GTR and to be a national product developed in low cost.
Use of biosynthetic cellulose membrane in the guided tissue regeneration
Keywords: guided tissue regeneration; articular cartilage; cellulose membrane